System Responsiveness to the Psychosocial and Mental Health Needs of Children in Ethiopian Primary Schools: The Case of Gondar City, Northwest Ethiopia Needs - Wondie, Yemataw; Tadele, Tesfaye (Frontiers in Sociology, 2021)
Background: Ethiopia is the second populous nation in Africa with children and adolescents constituting more than 40% of the population. Evidences show that the onset of significant degrees of mental illnesses is detectable in this age range. For this to be realized there should be a system responding to such needs. Objective: The objective of this study was to explore the extent to which the education system is responsive to the psychosocial and mental health needs of school children in primary schools through putting appropriate professionals in place, raising teachers’ awareness and putting in place viable policies and guild lines. Methods: An exploratory qualitative study was conducted on public and private primary schools in Gondar town. Data were collected through focus group discussions (FGD) from 17 discussants drawn from both schools and key informant interviews with 2 experts from the zonal Department of Education. A thematic qualitative data analysis was employed with themes identified by the Nvivo 12 plus software. Results: We found that teachers’ mental health awareness is very low seen against parameters such as magnitude, case identification and support except in terms of causal attributions of mental illness that sounds more of scientific. Psychosocial support and mental health resources are not also available. Regardless of this, schools do not provide capacity building mental health training to teachers that might help them to identify, handle and make referrals of mental health cases. We also found the Ethiopian education policy and other guidelines do not address the issue of mental health at primary school level. Conclusion: The Ethiopian education system is not responsive to the psychosocial and mental health needs of children in primary schools. Implications: Arresting minor impairments before they become major disabilities is vital. Investing on childhood mental health enables cultivating health and productive society. The Ethiopian education system should therefore respond to the psychosocial and mental health needs of children in primary schools.